An inclusive learning model to build toleration of diversity in primary school learners: a literature review - Retnasari , Lisa; Abdulkarim, Aim; Sundawa , Dadang; Bestari , Prayoga; Ella Kusuma Wardani (Universitas Ahmad Dahlan, 2024)
This article discusses innovations in inclusive-based learning models as an effort to shape tolerance towards diversity among learners in primary schools. In education, diversity is a necessity that requires an inclusive learning approach to create a supportive environment for all learners. This type of research is a qualitative literature study. Data collection is done by collecting references from various sources online. Furthermore, data analysis used the Miles and Huberman model: data reduction, display, and conclusion drawing. This approach not only includes ethnic, religious, and cultural diversity but also considers differences in abilities, learning styles, and special needs. This research discusses the positive impact of implementing an inclusive-based learning model on developing tolerance among learners. The results show that engaging learners in inclusive learning experiences can shape open attitudes, acceptance of differences, and increased understanding of diversity. The important role of educators is to support this learning model and provide practical advice for educators to implement it in the classroom. Thus, it is hoped that innovations in inclusive-based learning models can be an important foundation in shaping tolerance towards diversity among learners in primary schools